Clinical, Microbial, and Biochemical Aspects of the Exfoliative Toxins Causing Staphylococcal Scalded-Skin Syndrome - Ladhani, Shamez (American Society for Microbiology, 1999)
The exfoliative (epidermolytic) toxins of Staphylococcus aureus are the causative agents of the staphylococcal scalded-skin syndrome (SSSS), a blistering skin disorder that predominantly affects children. Clinical features of SSSS vary along a spectrum, ranging from a few localized blisters to generalized exfoliation covering almost the entire body. The toxins act specifically at the zona granulosa of the epidermis to produce the characteristic exfoliation, although the mechanism by which this is achieved is still poorly understood. Despite the availability of antibiotics, SSSS carries a significant mortality rate, particularly among neonates with secondary complications of epidermal loss and among adults with underlying diseases. The aim of this article is to provide a comprehensive review of the literature spanning more than a century and to cover all aspects of the disease. The epidemiology, clinical features, potential complications, risk factors, susceptibility, diagnosis, differential diagnoses, investigations currently available, treatment options, and preventive measures are all discussed in detail. Recent crystallographic data on the toxins has provided us with a clearer and more defined approach to studying the disease. Understanding their mode of action has important implications in future treatment and prevention of SSSS and other diseases, and knowledge of their specific site of action may provide a useful tool for physiologists, dermatologists, and pharmacologists.